Conductive silver paste and preparation method and application thereof

By combining silver powder, low-melting-point glass powder, and high-melting-point glass powder, the matching problem in the co-firing process of LTCC materials was solved, achieving low-cost conductivity and adhesion, and expanding the application range of LTCC devices.

CN119339987AInactive Publication Date: 2025-01-21CHINA BUILDING MATERIALS ACADEMY CO LTD
4 Cites 0 Cited by

Patent Information

Application Number
CN202411445835.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing LTCC materials suffer from poor matching between the silver layer and the ceramic substrate during co-firing, leading to problems such as warping, delamination, and cracking. Furthermore, the high cost of traditional gold paste limits its application range.

Method used

Conductive silver paste, which combines silver powder, low-melting-point glass powder, and high-melting-point glass powder, forms a dense film layer by controlling the Tg range and particle size of the glass powder. This improves the adhesion between the silver layer and the ceramic substrate and reduces the amount of gold paste used.

Benefits of technology

This achieves a good match between the silver layer and the ceramic substrate, avoiding warping and deformation, reducing production costs, while maintaining excellent conductivity and adhesion, thus expanding the application range of LTCC devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119339987A_ABST
    Figure CN119339987A_ABST
Patent Text Reader

Abstract

The invention relates to the field of low-temperature co-fired silver paste, in particular to conductive silver paste and a preparation method and application thereof. The chemical silver plating paste comprises the following components in parts by weight: 70-85 parts of a silver powder mixture, 0.2-5 parts of glass powder and 3.7-29.8 parts of an organic carrier, wherein the glass powder comprises low-melting glass powder with Tg not higher than 380 DEG C and high-melting glass powder with Tg not lower than 500 DEG C. According to the chemical silver plating paste and the preparation method thereof provided by the invention, not only is the use cost reduced, but also good flatness, electrical conductivity, compactness, adhesive force and other properties are maintained, so that the application range of LTCC devices is expanded, and a new development opportunity is brought to the industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of low-temperature co-fired silver paste, and in particular to a conductive silver paste and a preparation method and application thereof. Background Art

[0002] LTCC (low temperature co-fired ceramics), as the mainstream technology for passive integrated devices, has attracted widespread attention due to its excellent electrical properties and good thermal stability. However, traditional LTCC materials usually rely on the use of a large amount of gold paste, which not only significantly increases the production cost, but also limits its promotion in certain application fields. In contrast, if the silver layer can withstand the corrosion of the plating solution during the chemical plating process, gold can be plated on the surface of the silver wire of the substrate. In the preparation of the LTCC surface gold plating process, this method can not only meet the subsequent process requirements such as gold wire bonding, but also avoid the use of expensive gold paste, greatly reduce the cost of LTCC devices, and promote the promotion and application of LTCC packaging technology. Therefore, the research and development of related technologies has high production value and research significance.

[0003] However, chemical silver plating places higher demands on the co-firing matching of raw porcelain and slurry. Both LTCC raw porcelain and matching slurry will shrink during the co-firing process. If the sintering shrinkage of the two does not match, residual stress will be generated, which may cause the substrate to warp, delaminate and crack in severe cases. In addition, if the densification of the metal conductor thick film is completed too early, it will limit the discharge of gas during the densification process of the substrate, resulting in a large number of pores remaining at the interface between the metal conductor thick film and the substrate, affecting the density, flatness, adhesion and connectivity of the overall circuit of the thick film. These will lead to corrosion failure of the substrate during the chemical plating process. At present, there is an urgent need to provide a new chemically plated silver paste and a preparation method thereof. Summary of the invention

[0004] In order to solve the above problems, it is used for matching and co-firing LTCC green porcelain, and solves the problems of warping and weak bonding force of the existing silver paste and LTCC green porcelain co-firing, and realizes chemical gold plating on the substrate surface. The chemically plated silver paste and its preparation method provided by the present invention provide a more economical solution. This innovative method not only reduces the cost of use but also maintains good flatness, conductivity, density and adhesion, so that the application range of LTCC devices can be expanded, bringing new development opportunities to the industry.

[0005] In the first aspect, the conductive silver paste provided by the present invention comprises the following components in parts by weight: 70-85 parts of a silver powder mixture, 0.2-5 parts of a glass powder, and 3.7-29.8 parts of an organic vehicle; wherein the glass powder comprises a low-melting glass powder having a Tg not higher than 380°C and a high-melting glass powder having a Tg not lower than 500°C. In the present invention, the silver paste is prepared by preparing a silver powder mixture and matching two types of glass powders, low-melting and high-melting, and an organic vehicle, which can meet the silver paste's silver powder fluxing and leveling effect at low temperatures and during the debinding stage, while taking into account the inhibition of excessive leveling of the silver layer at high temperatures, ensuring that a dense film layer is produced after the silver paste is sintered, and the interaction between the glass powder and the oxide forms a firm network structure and the pinning effect to ensure the anti-peeling performance of the conductive film layer. The conductive silver paste prepared by the present invention has excellent flatness, conductivity and compactness after being co-fired with a LTCC ceramic substrate, has excellent chemical plating performance, thereby reducing the amount of gold paste used and reducing the use cost, and the silver layer has a strong tensile resistance, which can prevent the silver layer from separating from the ceramic substrate, can effectively improve the conductivity and adhesion of the conductive silver paste, and is used in the fields of electronic components, LTCC circuit boards, etc., and has high practical value and broad application prospects.

[0006] Preferably, it includes 75-85 parts of silver powder mixture, 0.5-4 parts of low-melting glass powder, 1-5 parts of high-melting glass powder, and 12-20 parts of organic carrier. For example, 78-84 parts of silver powder mixture, 0.5-3 parts of low-melting glass powder, 1-2.5 parts of high-melting glass powder, 13-18 parts of organic carrier, etc. The present invention limits the amount of silver powder mixture, low-melting glass powder, high-melting glass powder and organic carrier to a reasonable range value, so that the components can play a better synergistic role. The prepared silver paste is flat and dense after co-firing, has good solderability, solder resistance and strong substrate adhesion, and the effect is better within the preferred dosage range. The slurry can match LTCC raw porcelain tapes under various requirements, has higher printing quality on the raw porcelain surface, and the printing line width and accuracy are ≤100μm±10μm, has excellent co-firing matching, co-firing warpage ≤0.3%, and tin-lead welding strength ≥1.5kg.

[0007] Further preferably, the Tg of the low-melting glass powder is 200-380°C; and / or the Tg of the high-melting glass powder is 500-700°C. By limiting the Tg of the low-melting glass powder to 200-380°C, the mutual interference between the glass sintering and the organic binder removal stage can be better avoided to promote the leveling of the silver paste; while by limiting the Tg of the high-melting glass powder to 500-700°C, it is more conducive to avoiding excessive leveling of the silver layer and controlling the action time of the high-melting glass powder, thereby better controlling the sintered film layer structure and forming a denser sintered film layer.

[0008] It is further preferred that the mass ratio of the low-melting glass powder to the high-melting glass powder is 1:10-10:1, preferably 1:5-3:1; and / or the D50 of the glass powder is 1-3μm. For example, these values ​​can be 1.5μm, 2.0μm, 2.3μm, 2.5μm, 2.8μm, or any range between these values. By limiting the D50 particle size of the glass powder, it can effectively interact with the matching organic carrier, which is more conducive to the viscosity, dispersion and other control of the slurry. By optimizing the mass ratio of the glass powder, it is more conducive to the silver powder fluxing and leveling effect at low temperature and debinding stage, while taking into account the suppression of excessive leveling of the silver layer at high temperature.

[0009] Preferably, the raw materials of the silver powder mixture include silver powder, oxide, solvent and additive. The interaction between the low-melting glass powder and the oxide improves the surface bonding between the slurry and the LTCC green porcelain, so that it has excellent welding performance; the organic solvent forms a wide gradient of sintering volatilization and low carbon residue, which further improves the co-firing performance after sintering. Preferably, in the raw materials of the silver powder mixture, the mass ratio of the silver powder, oxide, organic solvent and additive is (84-92): (0.5-5): (3-10): (1-3); and / or, the silver powder includes one or more of spherical silver powder, quasi-spherical silver powder and polygonal rhombus silver powder; and / or, the oxide includes one or more of calcium oxide, aluminum oxide, cupric oxide, cuprous oxide, iron oxide, zinc oxide, fumed silica, manganese oxide and calcium lead titanate; and / or, the organic solvent includes one or more of α-pineneol, pineneol, alcohol ester dodecanedioate, dimethyl adipate, dimethyl glutarate and citrate; and / or, the additive includes one or more of 1-butene, polydimethylsiloxane, polyoxyethylene polyoxypropylene ether, polyoxyethylene ether, unsaturated fatty acid and alcohol ester. By controlling the mass ratio of the above-mentioned silver powder, oxide, organic solvent and additive within a suitable range, the organic coating on the surface of the prepared silver powder mixture is more uniform, the direct dispersion effect of the particles is stronger, the agglomeration effect between the powders is further reduced, the surface and internal tension of the powders are regulated, and the powders are fully dispersed.

[0010] More preferably, the silver powder has a D50 of 0.6-2.2 μm and a bulk density of 3.2-4.5 g / cm 2 , tap density is 5.0-7.0g / cm 2 By optimizing the particle size and density of the silver powder, the sintering temperature of the silver powder and the glass powder are matched with each other, so that better synergy can be achieved and warping or holes can be avoided after co-firing.

[0011] Preferably, the raw material of the organic carrier includes a binder, an additive and an organic solvent; preferably, in the raw material of the organic carrier, the mass ratio of the binder, the additive and the organic solvent is 0.5-5: 0.2-3.5: 3-25; and / or, the organic solvent includes one or more of α-terpineol, terpineol, alcohol ester dodecanedioate, dimethyl adipate, dimethyl glutarate and citrate; and / or, the additive includes one or more of 1-butene, polydimethylsiloxane, polyoxyethylene polyoxypropylene ether, polyoxyethylene ether, unsaturated fatty acid and alcohol ester; and / or, the binder is ethyl cellulose and / or hydroxyethyl cellulose. The present invention can effectively improve the rheological properties and printing properties of the slurry and improve the adhesion strength with the substrate by selecting an organic carrier of suitable components and reasonably selecting the component type of the organic carrier, optimize the surface density, and is conducive to the improvement of the overall performance of the silver paste, ensuring that the chemical plating process can be carried out.

[0012] More preferably, the molecular weight of the binder is 20000-70000; and / or the mass ratio of the ethyl cellulose to the hydroxyethyl cellulose is (0-1):(0-1).

[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned conductive paste, comprising mixing and rolling the silver powder mixture, the organic carrier and the glass powder. In the present invention, by using a combination of low-melting glass powder and high-melting glass powder, the density of the conductive film layer is further improved by fluxing the silver powder for leveling and pinning the silver film, respectively, so that a conductive silver paste with excellent performance can be obtained. In particular, by using the interaction between glass powder and oxide, the surface bonding force between the conductive silver paste and the LTCC raw porcelain is further improved, so that it has excellent welding performance. In addition, the improved silver paste also has significant improvements in printing accuracy and uniformity, ensuring the stability and reliability of electronic components.

[0014] Preferably, after the ingredients are mixed, they are stirred and degassed at high speed with a homogenizer to form a paste, and the paste is rolled 5-10 times with a three-roller mill, and the minimum rolling gap of the three-roller mill is 8-10 μm. The high-speed stirring and degassing treatment by the homogenizer is more conducive to the mutual mixing of the components to further improve the degree of dispersion, and avoid the use of additional degassing agents, thereby interfering with other components and reducing the grayscale after sintering. The rolling treatment of the three-roller mill can better improve the internal dispersibility of the slurry, significantly reduce the particle size, break up the agglomerated particles, and better regulate the fineness of the slurry. This homogenized slurry provides a good foundation for further processing of the material.

[0015] Preferably, the silver powder mixture is mixed, ball-milled, and filtered by silver powder, oxide, solvent, and additive; preferably, the silver powder, oxide, pinene alcohol, and additive are added to an agate pot and mixed for 30-35 minutes, so that the powder is fully mixed and coated by organic matter and fully mixed and dispersed uniformly, and the mixed liquid after mixing is filtered by suction equipment. The present invention uses the preliminary treatment of silver powder and oxide, and the process optimization makes the organic matter fully coated on the surface of inorganic powder, and then uses the suction filtration equipment to filter it so that it has excellent powder surface wetting tension and improves the dispersion degree between powders, thereby improving the full combination of inorganic and organic in the slurry to enhance the dispersion effect. The present invention obtains a suitable silver powder mixture, which can ensure that the powder is fully dispersed in the slurry organic carrier in the subsequent slurry configuration process and fully contacts, and by limiting the mixing time, it is beneficial to narrow the powder particle size range and reduce the formation of pores caused by insufficient sintering of large particles during the sintering process. The surface tension of the powder is further improved by suction filtration, the contact effect is improved, and the subsequent component weight control is conducive.

[0016] Preferably, the preparation of the organic carrier comprises mixing the organic solvent and the binder, stirring at high speed in a 75-80°C water bath for 1.5-2h, and fully dissolving the binder in the organic solvent; then cooling to 45-50°C, adding the additive during stirring, and continuing stirring for 10-12min.

[0017] In the third aspect, the present invention provides the use of the above-mentioned conductive paste or the conductive paste obtained by the above-mentioned preparation method in the preparation of electronic components and LTCC circuit boards. The conductive silver paste provided by the present invention is a mixture of silver powder and is matched with two kinds of glass powders with low melting point and high melting point and an organic carrier, which can meet the silver paste's silver powder fluxing and leveling effect at low temperature and debinding stage and take into account the suppression of excessive leveling of the silver layer at high temperature, ensuring that a dense film layer is produced after the silver paste is sintered, and a firm network structure is formed through the interaction between the two glass powders and the oxide, and the anti-peeling performance of the conductive film layer is ensured by the pinning effect. After the conductive silver paste is co-fired with the LTCC ceramic substrate, it has excellent flatness, conductivity and density, and has excellent chemical plating performance, thereby reducing the use of gold paste and reducing the use cost. At the same time, the silver layer has a strong tensile resistance, which has the advantage of avoiding the separation of the silver layer and the ceramic substrate, and can effectively improve the conductivity and adhesion of the conductive silver paste.

[0018] The beneficial effects of the present invention are at least that: the conductive silver paste provided by the present invention has excellent process performance, the printed pattern is precise and excellent, the paste has good conductivity and excellent soldering tensile performance after sintering with LTCC, and can form a dense paste layer, the paste and LTCC green porcelain are matched after co-firing, and there will be no warping, cracking, blistering and other defects of the substrate caused by co-firing mismatch. The silver paste of the present invention has excellent performance and can be subjected to chemical plating process, which can better meet the design and use requirements of precision LTCC devices, and can also avoid the use of expensive gold paste, greatly reducing the cost of LTCC devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 Comparison chart of printing test between silver paste provided in the embodiments of the present invention and LTCC raw ceramic tape (ac are embodiments 1-3, d is comparative example 1).

[0021] Figure 2 Microscopic pictures of the silver paste provided in the embodiments of the present invention after co-firing with the LTCC green ceramic tape (ac are embodiments 1-3, d is comparative example 1).

[0022] Figure 3 High temperature microscope curve diagram of two kinds of glass powders used in the silver paste provided in the embodiment of the present invention (a is low-melting glass powder, b is high-melting glass powder). DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer is not specified for the instruments used, they are all conventional products that can be purchased through regular channels. The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used.

[0026] In the following examples of the present invention, the Tg of the low-melting glass powder is 200-380°C ( Figure 3 a), the Tg of the high melting glass powder is 500-700°C ( Figure 3 b).

[0027] Example 1

[0028] This embodiment provides a chemically plating silver paste and a preparation method thereof, as described below.

[0029] Preparation of silver powder mixture: Weigh 90 parts of 2.2 μm silver powder, 1 part of copper oxide, 3 parts of aluminum oxide, 4 parts of pine alcohol, and 2 parts of polyoxyethylene polyoxypropylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes, and filter the paste after ball milling.

[0030] Preparation of organic carrier: weigh 50 parts of α-terpineol, 20 parts of alcohol ester dodecanedioate, and 17 parts of dimethyl glutarate, add them to a container and mix, put the container into a constant temperature water bath at 80°C, stir uniformly, add 10 parts of ethyl cellulose, stir uniformly for 90 minutes, after the ethyl cellulose is completely dissolved, cool to 45°C, stir, add 1 part of 1-butene, 1.5 parts of polydimethylsiloxane, and 1.5 parts of unsaturated fatty acids. Stir uniformly for 10 minutes and then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0031] Preparation of silver paste: weigh 84 parts of silver powder mixture, 13 parts of organic vehicle, 1 part of low-melting glass powder with D50 of 2 μm, and 2 parts of high-melting glass powder with D50 of 2 μm. Mix the above ingredients, stir and degas with a homogenizer at high speed, adjust to a paste, and roll the paste 8 times with a three-roll mill, with the minimum rolling gap of the three-roll mill being 10 μm to obtain the silver paste of Example 1 with moderate viscosity.

[0032] Example 2

[0033] This embodiment provides a chemically plating silver paste and a preparation method thereof, as described below.

[0034] Preparation of silver powder mixture: Weigh 88 parts of 0.6 μm silver powder, 1 part of copper oxide, 1 part of fumed silica, 7 parts of pineol, and 3 parts of polyoxyethylene polyoxypropylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes. Filter the paste after ball milling.

[0035] Preparation of organic carrier: Weigh 40 parts of α-terpineol, 20 parts of alcohol ester dodecanedioate, 20 parts of dimethyl glutarate, and 5 parts of citrate ester and add them to a container and mix them. Place the container in a constant temperature water bath at 80°C and stir uniformly. Add 6 parts of ethyl cellulose and stir uniformly for 90 minutes. After the ethyl cellulose is completely dissolved, cool to 45°C and stir. Add 4 parts of 1-butene, 4 parts of polydimethylsiloxane, and 1 part of unsaturated fatty acid. Stir uniformly for 10 minutes and then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0036] Preparation of silver paste: weigh 78 parts of silver powder mixture, 18 parts of organic vehicle, 3 parts of low-melting glass powder with D50 of 1.5 μm, and 1 part of high-melting glass powder with D50 of 2.3 μm. Mix the above ingredients, stir and degas with a homogenizer at high speed, adjust to a paste, and roll the paste with a three-roll mill for 8 times, with the minimum gap of the three-roll mill being 10 μm to obtain a silver paste of Example 2 with moderate viscosity.

[0037] Example 3

[0038] This embodiment provides a chemically plating silver paste and a preparation method thereof, as described below.

[0039] Preparation of silver powder mixture: Weigh 90 parts of 1.2 μm silver powder, 1 part of copper oxide, 3 parts of calcium lead titanate, 4 parts of pineol, and 2 parts of polyoxyethylene polyoxypropylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes. Filter the paste after ball grinding.

[0040] Preparation of organic carrier: weigh 50 parts of α-terpineol, 15 parts of alcohol ester dodecanedioate, 10 parts of dimethyl glutarate, and 5 parts of citrate ester, add to a container and mix, put the container into a constant temperature water bath at 80°C, stir uniformly, add 5 parts of ethyl cellulose and 5 parts of hydroxyethyl cellulose, stir uniformly for 90 minutes, after the ethyl cellulose is completely dissolved, cool to 45°C, stir, add 6 parts of 1-butene, 2 parts of polydimethylsiloxane, and 2 parts of unsaturated fatty acids. Stir uniformly for 10 minutes and then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0041] Preparation of silver paste: weigh 80 parts of silver powder mixture, 17 parts of organic vehicle, 0.5 parts of low-melting glass powder with a D50 of 1.5 μm, and 2.5 parts of high-melting glass powder with a D50 of 2.3 μm. Mix the above ingredients, stir and degas with a homogenizer at high speed, adjust to a paste, and roll the paste 8 times with a three-roll mill, with the minimum gap of the three-roll mill being 10 μm to obtain a silver paste of Example 3 with moderate viscosity.

[0042] Example 4

[0043] This embodiment provides a chemically plating silver paste and a preparation method thereof, as described below.

[0044] Preparation of silver powder mixture: Weigh 85 parts of 1.8 μm silver powder, 4 parts of cuprous oxide, 1 part of fumed silica, 7 parts of pine alcohol, and 3 parts of polyoxyethylene polyoxypropylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes. Filter the paste after ball milling.

[0045] Preparation of organic carrier: weigh 40 parts of α-terpineol, 15 parts of alcohol ester dodecanedioate, 22 parts of dimethyl glutarate, and 8 parts of citrate ester, add them to a container and mix, put the container into a constant temperature water bath at 80°C, stir uniformly, add 6 parts of ethyl cellulose, stir uniformly for 90 minutes, after the ethyl cellulose is completely dissolved, cool to 45°C, stir, add 4 parts of 1-butene, 4 parts of polydimethylsiloxane, and 1 part of unsaturated fatty acid. Stir uniformly for 10 minutes and then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0046] Preparation of silver paste: weigh 84 parts of silver powder mixture, 13 parts of organic vehicle, 1.5 parts of low-melting glass powder with D50 of 1.5 μm, and 1.5 parts of high-melting glass powder with D50 of 2.3 μm. Mix the above ingredients, stir and degas with a homogenizer at high speed, adjust to a paste, and roll the paste with a three-roll mill for 10 times, with the minimum gap of the three-roll mill being 10 μm to obtain a silver paste of Example 4 with moderate viscosity.

[0047] Example 5

[0048] This embodiment provides a chemically plating silver paste and a preparation method thereof, as described below.

[0049] Preparation of silver powder mixture: Weigh 88 parts of 1.2 μm silver powder, 1 part of copper oxide, 1 part of fumed silica, 7 parts of pineol, and 3 parts of polyoxyethylene polyoxypropylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes. Filter the paste after ball grinding.

[0050] Preparation of organic carrier: Weigh 40 parts of terpineol, 24 parts of alcohol ester dodecanedioate, 20 parts of dimethyl glutarate, and 5 parts of citrate ester and add them to a container and mix them. Place the container in a constant temperature water bath at 80°C and stir uniformly. Add 6 parts of hydroxyethyl cellulose and stir uniformly for 90 minutes. After the ethyl cellulose is completely dissolved, cool to 45°C and stir and add 2 parts of 1-butene, 2 parts of polydimethylsiloxane, and 1 part of unsaturated fatty acid. Stir uniformly for 10 minutes and then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0051] Preparation of silver paste: weigh 78 parts of silver powder mixture, 18 parts of organic vehicle, 3 parts of low-melting glass powder with D50 of 1.5 μm, and 1 part of high-melting glass powder with D50 of 2.3 μm. Mix the above ingredients, stir and degas with a homogenizer at high speed, adjust to a paste, and roll the paste 8 times with a three-roll mill, with the minimum gap of the three-roll mill being 10 μm to obtain a silver paste of Example 5 with moderate viscosity.

[0052] Example 6

[0053] This embodiment provides a chemically plating silver paste and a preparation method thereof, as described below.

[0054] Preparation of silver powder mixture: Weigh 84 parts of 1.8 μm silver powder, 3 parts of cuprous oxide, 10 parts of pine alcohol, and 3 parts of polyoxyethylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes. Filter the paste after ball grinding.

[0055] Preparation of organic carrier: weigh 30 parts of terpineol, 40 parts of alcohol ester dodecahydrate, and 20 parts of dimethyl adipate, add them to a container and mix them, put the container into a constant temperature water bath at 80°C, stir at a constant speed, add 5 parts of ethyl cellulose, stir at a constant speed for 90 minutes, after the ethyl cellulose is completely dissolved, cool to 45°C, stir, add 2 parts of 1-butene, 2 parts of polydimethylsiloxane, and 1 part of unsaturated fatty acid. Stir at a constant speed for 10 minutes, then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0056] Preparation of silver paste: weigh 80 parts of silver powder mixture, 16 parts of organic vehicle, 2.5 parts of low-melting glass powder with D50 of 1.5 μm, and 1.5 parts of high-melting glass powder with D50 of 2.3 μm. Mix the above ingredients, stir and degas with a homogenizer at high speed, adjust to a paste, and roll the paste 8 times with a three-roll mill, with the minimum rolling gap of the three-roll mill being 10 μm to obtain a silver paste of Example 6 with moderate viscosity.

[0057] Example 7

[0058] Preparation of silver powder mixture: Weigh 90 parts of 2.2 μm silver powder, 2 parts of copper oxide, 2 parts of aluminum oxide, 4 parts of pine alcohol, and 2 parts of polyoxyethylene polyoxypropylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes, and filter the paste after ball milling.

[0059] Preparation of organic carrier: weigh 50 parts of terpineol, 25 parts of alcohol ester dodecahydrate, and 15 parts of dimethyl adipate, add them to a container and mix them, put the container into a constant temperature water bath at 80°C, stir at a constant speed, add 5 parts of ethyl cellulose, stir at a constant speed for 90 minutes, after the ethyl cellulose is completely dissolved, cool to 45°C, stir, add 2 parts of 1-butene, 2 parts of polydimethylsiloxane, and 1 part of unsaturated fatty acid. Stir at a constant speed for 10 minutes, then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0060] Preparation of silver paste: weigh 82 parts of silver powder mixture, 16.5 parts of organic vehicle, 0.5 parts of low-melting glass powder with D50 of 1.5 μm, and 1 part of high-melting glass powder with D50 of 2.3 μm. Mix the above ingredients, stir and degas with a homogenizer at high speed, adjust to a paste, and roll the paste with a three-roll mill for 10 times, with the minimum gap of the three-roll mill being 10 μm to obtain a silver paste of Example 7 with moderate viscosity.

[0061] Comparative Example 1

[0062] This comparative example provides a LTCC silver paste and a preparation method thereof, which are specifically as follows.

[0063] Preparation of silver powder mixture: Weigh 90 parts of 1.8 μm silver powder, 1 part of copper oxide, 4 parts of pine alcohol, and 5 parts of polyoxyethylene polyoxypropylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes. Filter the paste after ball grinding.

[0064] Preparation of organic carrier: Weigh 40 parts of α-terpineol, 25 parts of alcohol ester dodecanedioate, 10 parts of dimethyl glutarate, and 5 parts of citrate ester and add them to a container and mix them. Place the container in a constant temperature water bath at 80°C and stir uniformly. Add 5 parts of ethyl cellulose and 5 parts of hydroxyethyl cellulose. Stir uniformly for 90 minutes. After the ethyl cellulose is completely dissolved, cool to 45°C and stir. Add 6 parts of 1-butene, 2 parts of polydimethylsiloxane, and 2 parts of unsaturated fatty acids. Stir uniformly for 10 minutes and then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0065] Preparation of silver paste: weigh 80 parts of silver powder mixture, 16 parts of organic vehicle, and 4 parts of low-melting glass powder with a D50 of 1 μm, wherein the low-melting glass powder is characterized by high temperature microscopy as follows Figure 3 The above ingredients were mixed, stirred and degassed with a homogenizer at high speed, and adjusted into a paste, and the paste was rolled 10 times with a three-roll mill, and the minimum rolling gap of the three-roll mill was 10 μm to obtain a comparative example 1 silver paste with moderate viscosity.

[0066] Comparative Example 2

[0067] This comparative example provides a LTCC silver paste and a preparation method thereof, which are specifically as follows.

[0068] Preparation of silver powder mixture: Weigh 93 parts of 1.2 μm silver powder, 1 part of cuprous oxide, 4 parts of pineol, and 2 parts of polyoxyethylene polyoxypropylene ether and place them in an agate jar together with agate balls. Transfer the agate jar to an omnidirectional planetary mill and mix and grind for 30 minutes. Filter the paste after ball milling.

[0069] Preparation of organic carrier: weigh 50 parts of α-terpineol, 15 parts of alcohol ester dodecanedioate, 10 parts of dimethyl glutarate, and 5 parts of citrate ester, add to a container and mix, put the container into a constant temperature water bath at 80°C, stir uniformly, add 5 parts of ethyl cellulose and 5 parts of hydroxyethyl cellulose, stir uniformly for 90 minutes, after the ethyl cellulose is completely dissolved, cool to 45°C, stir, add 6 parts of 1-butene, 2 parts of polydimethylsiloxane, and 2 parts of unsaturated fatty acids. Stir uniformly for 10 minutes and then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0070] Preparation of silver paste: weigh 80 parts of silver powder mixture, 16 parts of organic vehicle, and 4 parts of high-melting glass powder with a D50 of 3 μm, wherein the high-melting glass powder is characterized by high-temperature microscopy as follows Figure 3 The above ingredients were mixed, stirred and degassed with a homogenizer at high speed, and adjusted into a paste, and the paste was rolled 10 times with a three-roll mill, and the minimum rolling gap of the three-roll mill was 10 μm to obtain a comparative example 2 silver paste with moderate viscosity.

[0071] Comparative Example 3

[0072] This comparative example provides a chemical silver plating paste and a preparation method thereof, which are specifically as follows.

[0073] Preparation of organic carrier: Weigh 45 parts of terpineol, 20 parts of alcohol ester dodecanedioate, 10 parts of dimethyl glutarate, and 5 parts of citrate ester and add them to a container and mix them. Place the container in a constant temperature water bath at 80°C and stir at a constant speed. Add 5 parts of ethyl cellulose and 5 parts of hydroxyethyl cellulose. Stir at a constant speed for 90 minutes. After the ethyl cellulose is completely dissolved, cool to 45°C and stir and add 6 parts of 1-butene, 2 parts of polydimethylsiloxane, and 2 parts of unsaturated fatty acids. Stir at a constant speed for 10 minutes and then cool to room temperature to obtain an organic carrier with moderate viscosity.

[0074] Preparation of silver paste: weigh 80 parts of silver powder, 17 parts of organic vehicle, 0.5 parts of low-melting glass powder with a D50 of 1 μm, and 2.5 parts of high-melting glass powder with a D50 of 3 μm. Mix the above ingredients, stir and degas with a homogenizer at high speed, adjust to a paste, and roll the paste 8 times with a three-roll mill, with the minimum rolling gap of the three-roll mill being 10 μm to obtain a comparative example 3 silver paste with moderate viscosity.

[0075] Table 1 Performance of different silver pastes

[0076] Table 2 Properties of different silver pastes after co-firing with LTCC green porcelain

[0077] The performance of the slurry of Examples 1-7 and the comparative group before and after sintering is shown in Table 1 and Table 2. In the printing process, Examples 1-7 and Comparative Examples 1-3 all use the same screen (400 mesh, 30N tension) to mechanically print by a printer under the same printing parameters, and are co-fired with LTCC green porcelain at 850°C through the same sintering furnace and heating system. By comparing with the comparative examples, Examples 1-7 all show better printing thickness after printing. The smaller printing thickness can have better pattern stability when the green porcelain stack is subsequently prepared, and the printed graphics are more neat, and the printed graphics lack the jagged edges left by screen printing (such as Figure 1 ac), Comparative Examples 1-3 showed surface holes after printing, and the edges of the printed graphics were obviously jagged (such as Figure 1 d).

[0078] After being co-fired with LTCC green ceramics, Example 1-7 has very good conductivity, and the lower resistance can better meet the preparation requirements of precision devices. Under the condition that other properties are not affected, the ability of the slurry to bind to the LTCC surface is greatly improved. After being co-fired with LTCC green ceramics, Example 1-7 forms a flat and dense conductive layer (such as Figure 2 ac), in comparative examples 1-3, it was found that the surface of the slurry would leak porcelain and glass would float after sintering, which is one of the reasons for the high resistance and low soldering strength (such as Figure 2 d).

[0079] In summary, the silver paste prepared by the present invention has excellent process performance, the printed pattern is precise and excellent, the paste has good electrical conductivity and excellent soldering tensile performance after sintering with LTCC at 850°C and can form a dense paste layer, the paste itself matches the LTCC green porcelain co-firing, and will not produce defects such as warping, cracking, and blistering of the substrate due to co-firing mismatch.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A conductive silver paste, characterized in that: The invention comprises the following components in parts by weight: 70-85 parts of a silver powder mixture, 0.2-5 parts of a glass powder, and 3.7-29.8 parts of an organic carrier; wherein the glass powder comprises a low-melting glass powder with a Tg not higher than 380°C and a high-melting glass powder with a Tg not lower than 500°C.

2. The conductive silver paste according to claim 1, characterized in that: The invention comprises 75-85 parts of silver powder mixture, 0.5-4 parts of low-melting glass powder, 1-5 parts of high-melting glass powder and 12-20 parts of organic carrier.

3. The conductive silver paste according to claim 1 or 2, characterized in that: The Tg of the low-melting glass powder is 200-380°C; and / or the Tg of the high-melting glass powder is 500-700°C.

4. The conductive silver paste according to any one of claims 1 to 3, characterized in that: The mass ratio of the low-melting glass powder to the high-melting glass powder is 1:10-10:1; and / or the D50 of the glass powder is 1-3 μm.

5. The conductive silver paste according to any one of claims 1 to 4, characterized in that: The raw materials of the silver powder mixture include silver powder, oxides, solvents and additives; and / or, the silver powder includes one or more of spherical silver powder, quasi-spherical silver powder and polygonal rhombus silver powder; and / or, the oxide includes one or more of calcium oxide, aluminum oxide, cupric oxide, cuprous oxide, iron oxide, zinc oxide, fumed silica, manganese oxide and calcium lead titanate; and / or, the organic solvent includes one or more of α-pineneol, pineneol, alcohol ester dodecanedioate, dimethyl adipate, dimethyl glutarate and citrate; and / or, the additive includes one or more of 1-butene, polydimethylsiloxane, polyoxyethylene polyoxypropylene ether, polyoxyethylene ether, unsaturated fatty acids and alcohol esters.

6. The conductive silver paste according to claim 5, characterized in that: The silver powder has a D50 of 0.6-2.2 μm and a bulk density of 3.2-4.5 g / cm 2 , tap density is 5.0-7.0g / cm 2 .

7. The conductive silver paste according to any one of claims 1 to 6, characterized in that: The raw materials of the organic carrier include a binder, an additive and an organic solvent; preferably, in the raw materials of the organic carrier, the mass ratio of the binder, the additive and the organic solvent is (0.5-5): (0.2-3.5): (3-25); and / or, the organic solvent includes one or more of α-terpineol, terpineol, alcohol ester dodecanedioate, dimethyl adipate, dimethyl glutarate and citrate; and / or, the additive includes one or more of 1-butene, polydimethylsiloxane, polyoxyethylene polyoxypropylene ether, polyoxyethylene ether, unsaturated fatty acid and alcohol ester; and / or, the binder is ethyl cellulose and / or hydroxyethyl cellulose.

8. The conductive silver paste according to claim 7, characterized in that: The molecular weight of the binder is 20000-70000; and / or the mass ratio of the ethyl cellulose to the hydroxyethyl cellulose is (0-1):(0-1).

9. The method for preparing the conductive paste according to any one of claims 1 to 8, characterized in that: The method comprises mixing and rolling the silver powder mixture, the organic carrier and the glass powder.

10. Use of the conductive paste according to any one of claims 1 to 8 or the conductive paste obtained by the preparation method according to claim 9 in the preparation of electronic components and LTCC circuit boards.

Citation Information

Patent Citations

  • Low-resistance high-efficiency lead-free back silver pulp for amorphous silicon solar battery

    CN104505139A

  • Double-component high-contact glass powder for solar front silver paste

    CN111268915A

  • Conductive silver paste for low-temperature co-fired ceramic surface electrode and preparation method of conductive silver paste

    CN115691855A

  • LTCC conductive silver paste and preparation method thereof

    CN115798781A